Alternatives to plastic mulch under micro sprinkler irrigation - TINCY T. J; Veena T. S; Vidhya A. K; Er. Asha Joseph (Guide) (Tavanur 2010 Department of Irrigation and Drainage Engineering)
Alternatives to plastic mulch under micro sprinkler irrigation
Alternatives to plastic mulch under micro sprinkler irrigation